Current insights into inherited bone marrow failure syndromes - Nack-Gyun Chung; Myungshin Kim (Korean Pediatric Society, 2014)
Inherited bone marrow failure syndrome (IBMFS) encompasses a heterogeneous and complex group of genetic disorders characterized by physical malformations, insufficient blood cell production, and increased risk of malignancies. They often have substantial phenotype overlap, and therefore, genotyping is often a critical means of establishing a diagnosis. Current advances in the field of IBMFSs have identified multiple genes associated with IBMFSs and their pathways: genes involved in ribosome biogenesis, such as those associated with Diamond-Blackfan anemia and Shwachman-Diamond syndrome; genes involved in telomere maintenance, such as dyskeratosis congenita genes; genes encoding neutrophil elastase or neutrophil adhesion and mobility associated with severe congenital neutropenia; and genes involved in DNA recombination repair, such as those associated with Fanconi anemia. Early and adequate genetic diagnosis is required for proper management and follow-up in clinical practice. Recent advances using new molecular technologies, including next generation sequencing (NGS), have helped identify new candidate genes associated with the development of bone marrow failure. Targeted NGS using panels of large numbers of genes is rapidly gaining potential for use as a cost-effective diagnostic tool for the identification of mutations in newly diagnosed patients. In this review, we have described recent insights into IBMFS and how they are advancing our understanding of the disease's pathophysiology; we have also discussed the possible implications they will have in clinical practice for Korean patients.